55 years of the Faculty of Philosophy - Milačić, Srećko P. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
Speech of Mr Srećko Milačić, rector of the University of Priština with temporary Head-office in Kosovska Mitrovica